2010
DOI: 10.1002/14651858.cd008335.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pegloticase for chronic gout

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Pegloticase is a more recently approved pegylated mammalian recombinant uricase produced by a genetically modified strain of Escherichia coli that is approved in the United States for treatment of chronic treatment-resistant gout (79). It is not approved for treatment of TLS, and its use in this setting has not been reported.…”
Section: Recombinant Urate Oxidasementioning
confidence: 99%
“…Pegloticase is a more recently approved pegylated mammalian recombinant uricase produced by a genetically modified strain of Escherichia coli that is approved in the United States for treatment of chronic treatment-resistant gout (79). It is not approved for treatment of TLS, and its use in this setting has not been reported.…”
Section: Recombinant Urate Oxidasementioning
confidence: 99%
“…In a Phase II clinical trial of 12 weeks (n = 41), patients were divided into four cohorts and received pegloticase during the 12 weeks at a dosage of 4 or 8 mg for every 2 weeks or 8 or 12 mg for every 4 weeks 4547. These data demonstrate that patients treated with 8 mg of pegloticase for every 2 or 4 weeks had a lytic, ie, very rapid and sustained reduction in plasma uric acid; 4 mg for every 2 weeks was not as effective, and 12 mg for every 4 weeks did not provide additional benefit compared with 8 mg for every 4 weeks.…”
Section: Pegloticase In Clinical Trialsmentioning
confidence: 99%
“…The most common underlying diagnosis in patients undergoing elective THA is osteoarthritis (OA), followed by osteonecrosis, congenital hip disorders, and inflammatory arthritis [2]. A systematic review of 67 studies with 2,593 patients with 3,277 hips concluded that osteonecrosis was not associated with higher revision rates after THA compared to the other underlying diagnoses [3], with minor exceptions.…”
Section: Introductionmentioning
confidence: 99%